2022
DOI: 10.1002/lary.30213
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors and Health Care Utilization in Pediatric Chronic Suppurative Otitis Media

Abstract: Objectives Access to and utilization of perioperative healthcare may influence outcomes in patients with chronic suppurative otitis media (CSOM); however, the influencing factors are poorly understood. The objective of this study was to assess the association of sociodemographic factors with perioperative health care utilization for pediatric CSOM patients. Methods We conducted a review on pediatric CSOM patients (≤18 years old) who underwent tympanoplasty with/without mastoidectomy between 2010 and 2020. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The design of the questionnaire used in the survey has been previously described in detail [25,26,31]. In brief, sociodemographic, health, and lifestyle confounders in mother-infant dyads, which are associated with the incidence of childhood otitis media [3,5], were included in the analyses as covariates. The data retrieval was performed using medical transcription reports and self-administered questionnaires [32][33][34].…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of the questionnaire used in the survey has been previously described in detail [25,26,31]. In brief, sociodemographic, health, and lifestyle confounders in mother-infant dyads, which are associated with the incidence of childhood otitis media [3,5], were included in the analyses as covariates. The data retrieval was performed using medical transcription reports and self-administered questionnaires [32][33][34].…”
Section: Covariatesmentioning
confidence: 99%
“…Otitis media encompasses a spectrum of diseases related to in ammation in the middle ear, including acute otitis media, otitis media with effusion, and chronic suppurative otitis media [1][2][3][4]. The condition is one of the most common diseases of childhood, with more than half of children experiencing it at least once before three years of age [2,3,5]. Additionally, Wald et al [6] reported that infants with a rst episode of otitis media early in life (aged < 12 months) are more susceptible to recurrent otitis media.…”
Section: Introductionmentioning
confidence: 99%